2019
DOI: 10.2134/age2018.09.0039
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Soil Nutrient–Plant–Herbivore Linkages: A Case Study from Two Poultry Litter–Amended Pastures in Northwest Arkansas

Abstract: Analysis of soils and forages across land scapes aids in targeted nutrient manage ment.• Soil and plant relationships were identi fied on two beef farms and spatial scales.• Higher soil nutrients favored bermuda grass growth compared with tall fescue.• Grid sampling size impacts soil test values and site management.• Feeding and grazing strategies affect nutrient excretion and nutrient loss spatially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In Mediterranean rangelands, the accumulation and persistence of soluble nitrogen, phosphorus, and potassium in the upper soil layer varies with nutrient and with local biogeochemical conditions (Vinograd et al, 2019). This variation in soil nutrient accumulation can favor certain species over others (Braden et al, 2019). Thus, specific traits related to the ability to exploit soil resources (e.g., size of zone explored by roots, root impact density, specific root length, root diameter—see Tardy et al, 2017) may explain the discrepancies between the two species.…”
Section: Discussionmentioning
confidence: 99%
“…In Mediterranean rangelands, the accumulation and persistence of soluble nitrogen, phosphorus, and potassium in the upper soil layer varies with nutrient and with local biogeochemical conditions (Vinograd et al, 2019). This variation in soil nutrient accumulation can favor certain species over others (Braden et al, 2019). Thus, specific traits related to the ability to exploit soil resources (e.g., size of zone explored by roots, root impact density, specific root length, root diameter—see Tardy et al, 2017) may explain the discrepancies between the two species.…”
Section: Discussionmentioning
confidence: 99%
“…Lai and Kumar [39] observed that light grazing and the positive influence of animal manure associated with light grazing minimized many of the heavy grazing soil quality reductions. Site-specific farming must consider the intrinsic variability of soils, in that soil uniqueness and its variation across the landscape presents both challenges and opportunities [42][43][44][45][46].…”
Section: Soil Quality Studies Focusing On Grazed Pasturesmentioning
confidence: 99%
“…The samples were air dried, ground, and passed through a 2-mm sieve to achieve a fine earth sample for laboratory analysis. Dissolved reactive P was extracted from a mixture of 2 g of soil and 20 ml of deionized water following the method of Self-Davis et al (1998) and described in Braden et al (2019). The filtered extract was analyzed for P that reacted with Murphy-Riley reagents (Murphy & Riley, 1962) using an Autosampler II (Skalar Analytical).…”
Section: Soil Sampling and Laboratory Analysismentioning
confidence: 99%
“…Producers generally apply poultry litter on the basis of N supply to meet a forage production target, usually exceeding 4.5 Mg ha −1 yr −1 (Ashworth et al, 2020;Braden et al, 2019;Scott, 1995). The ratio of N/P in litter is about 2.7:1 (1.2:1 N/P 2 O 5 ) (Beegle, 1988), but the ratio required for forage grasses is 7:1 to 8:1 (Ball et al, 2015).…”
Section: Introductionmentioning
confidence: 99%